DESIGN AND BUILD AN IOT-BASED SMART PARKING SYSTEM - Mahyul Muna; Atthariq; Muhammad Nasir; Malvina Marchese (Bulletin of Engineering Science, Technology and Industry, 2023)
A parking area is a place where consumers or the public can park their cars or vehicles in the empty spaces provided in the parking lot. Usually the parking area is filled with quite a lot of vehicles, so it is difficult to find empty parking spaces that are still available in the parking area, due to the density of cars or vehicles passing around the parking area who also want to find empty spaces that are still available to park their cars. This thesis aims to create a parking system that can be monitored via smartphone to determine the availability of parking slots. The parking system uses a raspberry pi microcontroller, an infrared sensor which functions to detect cars entering each parking space, LEDs are used as indicator lights to notify the status of each parking space. The results obtained from system testing are that the system has been successfully implemented as expected based on respondents' responses to the feasibility of an IoT-based intelligent parking system application using questionnaire data from 40 respondents indicating "Strongly Disagree = 0%", "Disagree = 0.5%" , “Neutral = 20.5%”, “Agree = 93.5%”, “Strongly Agree = 88%”. The maximum distance for infrared sensor detection is 80 cm. Meanwhile, the speed of obtaining data values ​​from the sensor also depends on the distance and voltage applied to the sensor.